Technological change in the Latin American metalworking industries. Results of a programme of case studies - Jorge Katz (CEPAL Review, 1983)
The metalworking industry is passing through a phase of out-and-out transformation in the international scenario. The rapid development of Japanese production and its penetration into European and United States markets, the gradual consolidation of the position of several ‘newly industrializing countries’ (NIC) like Brazil, Korea or Taiwan as manufacturers and exporters of various products of the industry in question, the dramatic irruption of robotics as one of the latest steps in the increasing automation of the production process, and the more and more intensive use of microelectronics in several of its phases, but above all the feeling that the changes now brewing -in the spheres of technology, organization, international trade, etc.- are of considerable magnitude, make this industry an unquestionably attractive field for economic analysis.